Open quantum system description of singlet-triplet qubits in quantum dots - Castelano, L. K.; Fanchini, F. F. [UNESP]; Berrada, K. (American Physical Society (APS), 2016)
We develop a theoretical model to describe the dissipative dynamics of singlet-triplet qubits in GaAs quantum dots. Using the concurrence experimentally obtained [Shulman, Science 336, 202 (2012)]SCIEAS0036-807510.1126/science.1217692 as a guide, we assume that each logical qubit fluctuates under the action of a random telegraph noise (RTN) that simulates the 1/fα noise. We also study the dynamics of concurrence as a function of the amplitude of the RTN, the correlation time of the RTN, the preparation time of states, and the two-qubit coupling. Furthermore, we show that the two-qubit coupling together with the preparation time strongly affect the entanglement dissipative dynamics and both physical quantities can be employed to enhance the entanglement between singlet-triplet qubits.